African Customary Marriages in South Africa and the Intricacies of a Mixed Legal System: Judicial (In)novatio or Confusio? - Rautenbach, Christa; du Plessis, Willemien (McGill Law Journal / Revue de droit de McGill, 2012)
South Africa has a mixed legal system comprised of transplanted European laws (the core being Roman-Dutch law, subsequently influenced by English common law) and indigenous laws, referred to as customary law. This mix is also evident in South Africa’s marriage laws, which can roughly be divided into two categories: civil marriages or unions, and African customary marriages. Since 1994, the developments in these two categories of marriage have been revolutionary. The case law reads like a jurisprudential chronicle of factual situations never contemplated by the legislator, and the judiciary must resort to innovation to solve the intricacies of a constitutionalized mixed legal system. To deal with the challenges posed by the interaction of two seemingly equal legal systems in one legal sphere, the courts have followed a variety of approaches including legal positivism, the application of common law principles, and, more recently, the notion of transformative constitutionalism. The primary aim of this essay is to discuss the sometimes innovative and at other times confusing approaches followed by the judiciary in dealing with the complexities created by a mixed legal system, especially with regard to marriages between Africans.